The rise of the network society - Castells, Manuel (Castells, Manuel, 2010)
This first book in Castells' groundbreaking trilogy, with a substantial new preface, highlights the economic and social dynamics of the information age and shows how the network society has now fully risen on a global scale. * Groundbreaking volume on the impact of the age of information on all aspects of society* Includes coverage of the influence of the internet and the net-economy* Describes the accelerating pace of innovation and social transformation* Based on research in the USA, Asia, Latin America, and Europe